2019
DOI: 10.1186/s40364-019-0169-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin as a biomarker for targeted therapy

Abstract: CAR-T cell therapy targeting CD19 has achieved remarkable success in the treatment of B cell malignancies, while various solid malignancies are still refractory for lack of suitable target. In recent years, a large number of studies have sought to find suitable targets with low “on target, off tumor” concern for the treatment of solid tumors. Mesothelin (MSLN), a tumor-associated antigen broadly overexpressed on various malignant tumor cells, while its expression is generally limited to normal mesothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 118 publications
(131 reference statements)
0
83
0
2
Order By: Relevance
“…antigen receptors (CAR) T cells have been developed and are believed to be promising therapeutics for patients with MSLN-expressing tumors (18). MSLN expression in immunohistochemistry is envisaged to be a suitable biomarker for predicting clinical response to these therapeutics, but its efficacy has never been fully evaluated.…”
Section: Diffuse Mesothelin Expression Leads To Worse Prognosis Throumentioning
confidence: 99%
See 1 more Smart Citation
“…antigen receptors (CAR) T cells have been developed and are believed to be promising therapeutics for patients with MSLN-expressing tumors (18). MSLN expression in immunohistochemistry is envisaged to be a suitable biomarker for predicting clinical response to these therapeutics, but its efficacy has never been fully evaluated.…”
Section: Diffuse Mesothelin Expression Leads To Worse Prognosis Throumentioning
confidence: 99%
“…Many anti-MSLN therapies such as a high-affinity chimeric monoclonal antibody (MORAb-009), recombinant immunotoxins (SS1P, RG7787/LMB-100), anti-MSLN antibody drug conjugates (anetumab ravtansine, DMOT4039A, BMS-986148), or adoptive T-cell immunotherapy using MSLN-specific CARs in autologous T lymphocytes are currently being investigated in phase I and II studies targeting advanced solid tumors including pancreatic cancer and malignant mesothelioma with high MSLN expression (18). In the present study, over half of the CRC patients showed tumor-specific MSLN expression.…”
Section: % CI -------------------------------------------------Varimentioning
confidence: 99%
“…MSLN is a glycoprotein expressed more on the cell surface of several tumors, including MPM cells, than in normal tissues (111). A phase II clinical trial (NCT00738582) testing amatuximab, a chimeric anti-MSLN mAb, plus standard CT compared to CT alone showed a promising OS of 14.8 months (112) that was not confirmed in the ARTEMIS trial (NCT02357147).…”
Section: Mesothelioma Targeting Antigensmentioning
confidence: 99%
“…A more detailed overview of anti-MSLN antibody-based drugs and vaccines can be found in a recent review by Lv J. & Li P [68].…”
Section: Anti-msln Cancer Vaccinesmentioning
confidence: 99%